The Role of Zakat in an Islamic Economic Perspective - Dhika ardhana; Garnis fajriah; Muhammad dalva al haq; Nabila rahmadania (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Zakat has a central role in the Islamic perspective, not only as a financial obligation, but also as an important instrument in social and economic development. Zakat is required as a form of worship to Allah SWT and as a means to help others. By providing a platform for Muslims to contribute to wealth redistribution, reduce economic inequality, and provide assistance to those deemed needy or underprivileged. Zakat is more than just a financial obligation, it reflects the social values of humanity and justice in Islam. In this context, zakat is not only about conducting financial transactions, but also carrying out tangible manifestations of worship and social responsibility of Muslims. In addition to strengthening solidarity, zakat can be used to support productive businesses, such as providing business capital to people in need, providing skills and ability training, or establishing Islamic financial institutions that provide interest-free loans to small entrepreneurs. Zakat can be used to finance social programs, such as infrastructure development, education, health, and social assistance to families in need. In addition, zakat has a role in cleansing wealth or wealth from greed. By making regular zakat payments, Islam teaches respect and sharing.